Microneedles: One-plane bevel-tipped fabrication by 3d-printing processes (2022)
This article presents microneedles analyses where the design parameters studied included length and inner and outer diameter ranges. A mathematical model was also used to generalize outer and inner diameter ratios in the obtained ranges. Following this, the range of inner and outer diameters was completed by mechanical simulations, ranging from 30 μm to 134 μm as the inner diameter range and 208 μm to 250 μm as the outer diameter range. With these ranges, a mathematical model was made using fourth-order polynomial regressions with a correlation of 0.9993, ensuring a safety factor of four in which von Misses forces of the microneedle are around 17.931 MPa; the ANSYS software was used to analyze the mechanical behavior of the microneedles. In addition, the microneedle concept was made by 3D printing using a bio-compatible resin of class 1. The features presented by the microneedle designed in this study make it a promising option for implementation in a transdermal drug-delivery device